中国花生国际贸易竞争力分析International trade competitiveness analysis of China′s peanut - 宋佳1,2，刘帅1,2 SONG Jia1,2, LIU Shuai1,2 (Zhongguo youzhi)
近年来，国际花生市场的贸易格局发生了重大变化，为探究新形势下中国花生国际贸易竞争力，促进花生产业健康发展，在分析中国花生贸易发展现状的基础上，通过国际市场占有率、贸易竞争力指数、显示性比较优势指数对比了当前中国与其他主要花生贸易国的出口竞争力，并从市场势力的角度，运用改进的依市定价（PTM）模型探讨当前中国花生在进口市场中的议价能力。结果表明：中国花生出口的产品结构虽有所优化，但在全球花生贸易竞争中仍呈现出竞争力进一步减弱的趋势；中国在对塞内加尔、印度和阿根廷的花生进口中存在市场势力，但因进口市场过于集中，总体进口风险仍然较高。综上，建议构建国际花生进口的风险评估预警和应急体系，推动中国花生产业集群化、规模化发展，多元化花生进出口结构，集中优势提高国际贸易竞争力。 In recent years, significant changes have taken place in the trade pattern of the international peanut market. In order to explore the international trade competitiveness of China′s peanut under the new situation and promote the healthy development of the peanut industry, based on the analysis of the development status of China′s peanut trade, the current export competitiveness of China and other major peanut trading countries was compared using metrics such as the international market share, trade competitiveness index, and revealed comparative advantage index. Furthermore, from the perspective of market power, an improved Pricing-to-Market (PTM) model was employed to discuss the current bargaining power of China′s peanut in the import market. The results showed that although the product structure of China′s peanut export had been optimized, it still showed a trend of further weakening competitiveness in the global peanut trade competition. China had market power in the import of peanuts from Senegal, India and Argentina, but the overall import risk was still high because the import market was too concentrated. To sum up, it is suggested to build a risk assessment, early warning and emergency response system for international peanut import, promote the clustering and large-scale development of China′s peanut industry, diversify the structure of peanut import and export, and concentrate advantages to improve the competitiveness of international trade.